Pranata Hukum Hibah - Lisdaleni Lisdaleni; Muyasaroh Muyasaroh (Jurnal Relasi Publik, 2023)
This article aims to analyze the legal institutions of grants so that readers will know what the true meaning of grants is, know the arguments in the grant law, know the pillars of grants and know the terms of grants. And later readers will be able to find out examples of grant letters and how to practice grant law in everyday life. The method used in this research uses a qualitative approach with the type of Library Research, namely data taken from journals, books, documents and online literature. This research data technique comes from books, journals and scientific articles related to grant legal institutions. Data analysis in this research uses Content Analysis technology, namely classifying or grouping data separately regarding the discussion of several ideas or ideas of educational figures, then describing, discussing and criticizing them. Additionally, classify similar data and critically analyze the content to obtain specific and adequate results.